Grants Scheme : 2006 Report. (Carrick Institute for Learning and Teaching in Higher Education, 2006)
The Grants Scheme enables the Australian Learning and Teaching Council Limited (ALTC) to realise its designated responsibility to provide grants for academics and professional staff to investigate, develop and implement innovations in learning and teaching, and to develop leadership capabilities. This report provides information about the scheme and the programs supported in 2006.